The Endothelium in Sepsis (2016)
Sepsis affects practically all aspects of endothelial cell (EC) function and is thought to be the key factor in the progression from sepsis to organ failure. Endothelial functions affected by sepsis include vasoregulation, barrier function, inflammation, and hemostasis. These are among other mechanisms often mediated by glycocalyx shedding, such as abnormal nitric oxide metabolism, up-regulation of reactive oxygen species generation due to down-regulation of endothelial-associated antioxidant defenses, transcellular communication, proteases, exposure of adhesion molecules, and activation of tissue factor. This review covers current insight in EC-associated hemostatic responses to sepsis and the EC response to inflammation. The endothelial cell lining is highly heterogeneous between different organ systems and consequently also in its response to sepsis. In this context, we discuss the response of the endothelial cell lining to sepsis in the kidney, liver, and lung. Finally, we discuss evidence as to whether the EC response to sepsis is adaptive or maladaptive. This study is a result of an Acute Dialysis Quality Initiative XIV Sepsis Workgroup meeting held in Bogota, Columbia, between October 12 and 15, 2014.